Training Induced Changes to Skeletal Muscle Passive Properties Are Evident in Both Single Fibers and Fiber Bundles in the Rat Hindlimb - Noonan, Alex M.; Mashouri, Parastoo; Chen, Jackey; Power, Geoffrey A.; Brown, Stephen H. M. (Frontiers in Physiology, 2020)
Introduction: The passive mechanical behavior of skeletal muscle represents both important, and generally underappreciated, biomechanical properties with little attention paid to their trainability. These experiments were designed to gain insight into the trainability of muscle passive mechanical properties in both single fibres and fibre bundles. Methods: Rats were trained in two groups: 4 weeks of either uphill (UH) or downhill (DH) treadmill running; with a third group as sedentary control. After sacrifice, the soleus (SOL), extensor digitorum longus (EDL), and vastus intermedius (VI) were harvested. 179 bundles and 185 fibres were tested and analyzed using a cumulative stretch-relaxation protocol to determine the passive stress and elastic modulus. Titin isoform expression was analysed using SDS-VAGE. Results: Single fibres: passive modulus and stress were greater for the EDL at sarcomere lengths (SLs) ≥ 3.7 µm (modulus) and 4.0 µm (stress) with DH compared to UH training, and lesser for the SOL (SLs ≥ 3.3 µm) with DH training compared with control; there was no effect of UH training. VI was not affected by either training protocol. Fibre bundles: passive modulus and stress were greater for the EDL at SLs ≥ 2.5 µm (modulus) and 3.3 µm (stress) in the DH training group as compared with control, while no affects were observed in either the SOL or VI for either training group. No effects on titin isoform size were detected with training. Conclusion: This study demonstrated a trainability of passive muscle properties at both the single fibre and fibre bundle levels were not accompanied by any detectable changes to titin isoform size.